If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -12y = 0 Solving 8x + -12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12y' to each side of the equation. 8x + -12y + 12y = 0 + 12y Combine like terms: -12y + 12y = 0 8x + 0 = 0 + 12y 8x = 0 + 12y Remove the zero: 8x = 12y Divide each side by '8'. x = 1.5y Simplifying x = 1.5y
| 4(1)+3(4)=19 | | 4(-7a+2)+10=-6+8a | | 4(n+1)=(11-n) | | 6*8-(3-7)+8*3= | | w^2=54 | | 4(6)+(-6)=-24 | | inx=-3 | | 7=w+7/7+4w-3/5 | | a(6)-2(-6)=-12 | | 9=5n-1 | | 3-2x=4x+1 | | -93-10=8x+15 | | 3=39y | | 3x-2(2-2x-8)=72 | | k/3=8 | | -44-(-99)= | | 7(n-5)-(2-3n)=9n | | 96=6u | | 4y+3x=5fory | | 4-12y+9y^2=0 | | s-1=22 | | -1=10z-4 | | 1cx+qy=t | | k^2-11k+28=0 | | 81-18x+x^2=0 | | 85-3x=24x+22 | | 12+1/3a=2 | | -4(-2)(-1)(6)= | | 4x+12=9x-12 | | 3(2x-1)+3=4x | | X^2-5+1=0 | | -x+6=26 |